BioV Suite - A collection of programs for the study of transport protein evolution - Reddy, Vamsee S. (2012)
The Bio-V Suite is a collection of python scripts designed specifically for bioinformatic research regarding transport protein evolution. The Bio-V Suite contains nine powerful programs for Unix-based environments, each of which can be run as a standalone tool or be accessed in a programmatic fashion. These programs and their functions are as follows: TMStats generates topological statistics for transport proteins. GSAT performs shuffle-based binary alignments and is fully scalable. It can cross compare two FASTA files or individual sequences. Protocol1 performs remote PSI-BLAST searches and filters redundant/similar sequences and annotates them. Protocol2 finds homologues between FASTA lists and generates graphical reports. TSSearch uses a rapid search algorithm to find distant homologues in FASTA files in a heuristic manner. SSearch is the exhuastive version of TSSearch. GBlast will identify potential transport proteins in any genome/proteome file, or find similar transport protein homologues between two different genomes/proteomes before generating a graphical report. AncientRep will find putative transmembrane repeat units using a list of homologues. DefineFamily will generate a FASTA list to represent an entire TC family. These nine programs are tabulated with descriptions of their capabilities in Table 1.